Serangan Ulat Grayak Jagung (Spodoptera Frugiperda) pada Tanaman Jagung di Desa Petir, Kecamatan Daramaga, Kabupatem Bogor dan Potensi Pengendaliannya Menggunakan Metarizhium Rileyi - Ahmad Aripin Naek Lubis1; Ruly Anwar; Bonny PW Soekarno; Bonjok Istiaji; Sartiami Dewi; Irmansyah; Dian Herawati (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) is a new pest in maize cropping inIndonesia. These insects originated in the Americas and have spread to several countries and causecrop loss in corn. Beginning in 2019, this pest has reportedly attacked corn plants in the Sumatraregion. This activity aims to find out the existence of S. frugiperda in the area of Petir Village,Dramaga Sub-District, Bogor District. The survey results show that S. frugiperda has attacked thecorn crop in Petir Village. Specific characters found in S. frugiperda are inverted "Y" in the headcapsule and a black dot pattern on the abdomen (point four and trapezoid). S. frugiperda larvae found in the village of Petir attack the corn growing point, but the population is still low. Entropathogenicfungi are bioinsecticides that can be used to control pests. Metarizhium rileyi is an entomopathogenicfungus that has the potential to control S. frugiperda in maize. The results indicated that M. rileyi waseasily propagated en masse in agar medium and in good virulence in S. frugiperda.